VIDEO BLOG AS THE DEVELOPING MEDIA OF WRITING RECOUNT TEXT FOR STUDENTS IN SENIOR HIGH SCHOOL - Fildzah Arifah and Anggraini Thesisia Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
This research was aimed to develop appropriate, interesting and attractive writing media in teaching recount text for ten grade students of Sinar Husni high school. The research was conducted by Research and Development (R & D) design through six stages; gathering information and data, analyzing data, designing media, validating by experts, revising, and final product. The subject of this research was class X-IPA students consisting of 39 students. The instruments for collecting the data were questionnaire and interview. The interview result was analyzed as qualitative data and the questionnaires analyzed as quantitative data. The interview and questionnaire results prove that the students need a media in learning recount text. The products have been validated by experts. The scores are 86,08% from English Lecturer and 92,17% from English Teacher. It means the developing media appropriate to teach recount text for the grade students of Sinar Husni high school.